Colonisation of ants on the exposed banks of the Canning Dam reservoir - Woodroff, S.; Majer, Jonathan (1981)
The plants, ants and certain epigaeic invertebrates were sampled on the banks of the Canning Dam reservoir which had become exposed as a result of several years drought. At least 26 plant and 17 ant species had colonised the reservoir banks within 67 months of exposure. All but three ants present were also residents of the adjacent forest. Most were generalist feeders which nested in soil or subterranean dead wood. The ant species present took between about 1.5 and 67 months to colonise the banks. The species composition of ants was very similar to those recolonising nearby bauxite mined areas.